Hydroxyapatite-Based Coating on Biomedical Implant - W. S., Wan Harun; Rahil Izzati, Mohd Asri; Abu Bakar, Sulong; S. A., Che Ghani; Z., Ghazalli (InTech, 2018)
The use of metallic biomaterials for replacement of biomedical implants has been traced back from the nineteenth century. These metallic biomaterials have been declared as clinical success as their mechanical properties that satisfy the prerequisite of the human bone. Nevertheless, critical issues of the materials when they are utilised as implants; including the releasing toxic and harmful metal ions through wear and corrosion processes after longer implantation. Besides that, the bonding strength between bone and implants itself is considered weak due to the different components of human bone and metal implants. Hence, developing hydroxyapatite (HAp) coating on metallic biomaterials is expected to overcome the problems faced by biocompatible metallic biomaterials. As far as this, various commercial techniques have been introduced to develop the HAp coating on metallic biomaterials. The techniques are including plasma-spraying method, sol-gel dip-coating, electrochemical deposition and high-velocity suspension plasma-spraying. The formation of HAp coating on metallic biomaterials improved the corrosion resistance together promoting its load-bearing ability and enhanced substrate-coating adhesion.